2021
DOI: 10.1016/j.xnsj.2021.100089
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, multicenter study of intraosseous basivertebral nerve ablation for the treatment of chronic low back pain: 24-Month treatment arm results

Abstract: on behalf of the INTRACEPT trial investigators, Prospective, randomized, multicenter study of intraosseous basivertebral nerve ablation for the treatment of chronic low back pain: 24-month treatment arm results,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…This appears to be supported by the existing literature, in which the vast majority of study participants observed to initially benefit from BVN RFA continued to report significant pain and functional improvement at 1, 2, and 5 years ( Figures 2–5 ). This pattern appears to be the same in industry-funded [ 3 , 7–10 , 36 ] and independently performed studies [ 1 , 5 ]. Along with robust improvements in pain and function, healthcare utilization appears to decrease substantially after BVN RFA.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This appears to be supported by the existing literature, in which the vast majority of study participants observed to initially benefit from BVN RFA continued to report significant pain and functional improvement at 1, 2, and 5 years ( Figures 2–5 ). This pattern appears to be the same in industry-funded [ 3 , 7–10 , 36 ] and independently performed studies [ 1 , 5 ]. Along with robust improvements in pain and function, healthcare utilization appears to decrease substantially after BVN RFA.…”
Section: Discussionmentioning
confidence: 60%
“…There were no disagreements among reviewers about study inclusion. These included one RCT comparing BVN RFA with sham, with outcomes reported at up to 1, 2, and 5 years [ 4 , 7 , 9 , 10 ]; one RCT comparing BVN RFA with standard care treatment, with outcomes reported at up to 3, 6, 12, and 24 months [ 8 , 11 , 36 ]; and four single-group cohort studies, with outcomes reported between 3 and 12 months [ 1 , 3 , 5 , 6 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence has driven the development of therapeutic interventions designed to denervate such pain generators. Such treatments substantially improve pain and function when provided to well-selected patients [ 11 , 12 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%